The Analysis of Moral Education on Rhoma Irama’s Song Lyrics - Defika Andriana Sari; Muhammad Yusuf (Journal of Research in Islamic Education, 2020)
This study is entitled "Analysis of Islamic Education Values ​​in Rhoma Irama Song Lyrics". The purpose of this research is to universally apply the meaning contained in song lyrics in the field of morals in daily activity. This type of research is a descriptive analysis. The research results are; 1) There is an element of the value of moral education for parents in the lyrics of the song 'Keramat', that everyone must have respect, obey their parents, because their prayers and blessings are very important; 2) There is an element of the value of moral education towards religion in the lyrics of the song 'Kematian', which means that in droves of good deeds, because in essence everything that God gives, will also return to Him; 3) the emergence of elements of the value of social moral education in the lyrics of the song 'Teman', that all created beings, in God's sight are the same, there is no difference. So there is no need for anyone to be proud, because life cannot be alone, of course it requires the help of others.